First Report of a Psyllid Vector of ‘Candidatus Phytoplasma pruni’ (Strain 16SrIII-J) - Tomás Llantén; Sebastián Cabrera; Javiera Fuentes; Camila Gamboa; Constanza González; Alan Zamorano; Tomislav Curkovic; Daniel Burckhardt; Nicola Fiore (Plants)
In Graneros, O’Higgins Region, Chile, the mallow psyllid (Russelliana solanicola Tuthill, 1959) from Malva nicaeensis L. was identified as a potential vector of ‘Candidatus Phytoplasma pruni’. Over an 8-month period, 2089 specimens of a species of Psylloidea, including immatures and adults, were captured. We only selected the adults used for transmission trials in Catharanthus roseus (L.) G. Don (periwinkle) plants. By nested PCR, using primer pairs for phytoplasma detection in 16S rRNA and IdpA genes, 7 out of 113 (6.2%) periwinkle plants used in transmission trials were found to be infected by phytoplasmas. Insects that fed on these plants also tested positive for the same phytoplasmas. Periwinkle plants never showed virescence and phyllody, as commonly occurs with phytoplasma 16SrIII-J infection due to the effector SAP54. In this case, using primer pairs for the SAP54 gene, an amplification product was never obtained. Virtual restriction fragment length polymorphism (RFLP) analysis of F2nR2 fragments indicated that the phytoplasma, found in both periwinkle plants and insects used in transmission trials, belongs to the 16SrIII-J ribosomal subgroup. The COI gene of the psyllids samples was amplified and sequenced, showing a similarity ranging from 84.84% to 85.02% with R. solanicola from Solanum tuberosum L. The mitochondrial genome of the psyllid was also sequenced, revealing a 14,835 bp circular DNA molecule with 37 genes. The mallow psyllid transmitted the phytoplasma 16SrIII-J to periwinkle plants. The molecular identification of the insect does not match the morphological one, indicating that the mallow psyllid may constitute a cryptic species within the polyphagous R. solanicola species. This is the first report of a psyllid as a vector of the phytoplasma 16SrIII-J.